Mycorrhizal preference promotes habitat invasion by a native Australian orchid: Microtis media - De Long, J.; Swarts, N.; Dixon, Kingsley; Egerton-Warburton, L. (2013)
Background and Aims: Mycorrhizal specialization has been shown to limit recruitment capacity in orchids, but an increasing number of orchids are being documented as invasive or weed-like. The reasons for this proliferation were examined by investigating mycorrhizal fungi and edaphic correlates of Microtis media, an Australian terrestrial orchid that is an aggressive ecosystem and horticultural weed. Methods: Molecular identification of fungi cultivated from M. media pelotons, symbiotic in vitro M. media seed germination assays, ex situ fungal baiting of M. media and co-occurring orchid taxa (Caladenia arenicola, Pterostylis sanguinea and Diuris magnifica) and soil physical and chemical analyses were undertaken. Key Results: It was found that: (1) M. media associates with a broad taxonomic spectrum of mycobionts including Piriformospora indica, Sebacina vermifera, Tulasnella calospora and Ceratobasidium sp.; (2) germination efficacy of mycorrhizal isolates was greater for fungi isolated from plants in disturbed than in natural habitats; (3) a higher percentage of M. media seeds germinate than D. magnifica, P. sanguinea or C. arenicola seeds when incubated with soil from M. media roots; and (4) M. media–mycorrhizal fungal associations show an unusual breadth of habitat tolerance, especially for soil phosphorus (P) fertility. Conclusions: The findings in M. media support the idea that invasive terrestrial orchids may associate with a diversity of fungi that are widespread and common, enhance seed germination in the host plant but not co-occurring orchid species and tolerate a range of habitats. These traits may provide the weedy orchid with a competitive advantage over co-occurring orchid species. If so, invasive orchids are likely to become more broadly distributed and increasingly colonize novel habitats.